2007
DOI: 10.2193/2006-385
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for Surveying Herpetofauna Mortality on Rural Highways

Abstract: Road mortality can contribute to local and regional declines in amphibian and reptile populations. Thus, there is a need to accurately and efficiently identify hotspots of road‐mortality for hazard assessment and mitigation. In 2002, we conducted walking and driving surveys throughout an extensive rural highway network in northern New York, USA, to evaluate survey methods and to quantify spatial and temporal patterns of herpetofauna road‐mortality. In 2004, we repeated the surveys at a subset of locations to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 26 publications
1
69
1
2
Order By: Relevance
“…Smaller objects are harder to detect than larger ones, especially when observing from a moving vehicle (Slater 2002;Ford and Fahrig 2007;Langen et al 2007). Further, small carcasses are more easily taken by a wider range of scavengers (Slater 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller objects are harder to detect than larger ones, especially when observing from a moving vehicle (Slater 2002;Ford and Fahrig 2007;Langen et al 2007). Further, small carcasses are more easily taken by a wider range of scavengers (Slater 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that our study, carried out in very favourable conditions (very low traffic allowing for detailed observation and two observers walking along the same section of the road twice), resulted in very high detection rates of killed individuals. What is more, we conducted surveys by walking only, while the data in Orłowski (2007) derives partly from driving surveys, a method that could have resulted in underestimation of the density of road mortality (Langen et al 2007) and does not make it possible to register juvenile amphibian victims. Hels and Buchwald (2001) highlighted just how relatively unreliable uncorrected road kill estimates might be, showing that up to 93% of certain amphibian road victims (Triturus vulgaris and Triturus cristatus) could be missed where a road is patrolled on foot once a day.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency estimates (DoR/km/survey) are assumed to be representative of daily mortality rates (i.e., DoR/ km/day) for birds, mammals, snakes, and amphibians, as other research has shown that most carcasses of these animals remain on the road for only one day (enge and Wood 2002;DeGregorio et al 2011;santos et al 2011). For turtles, however, per survey rates may not be synonymous with daily rates as some investigators have found most specimens remain on the road for two or more days (Langen et al 2007;santos et al 2011).…”
Section: Data Analysis and Mappingmentioning
confidence: 99%
“…in Canada, road mortality is now considered a major threat to the persistence of endangered species, particularly reptiles (e.g., Row et al 2007). Road mortality surveys have been used in areas of ecological importance to identify the nature and extent of wildlife road mortality (ashley and Robinson 1996; Vijayakumar et al 2001;smith and Dodd 2003;Langen et al 2007;Coelho et al 2008;shepard et al 2008), and to measure the effectiveness of mitigation measures (Dodd et al 2004;aresco 2005;BaxterGilbert et al 2015).…”
Section: Introductionmentioning
confidence: 99%